Estimating monetary conditions index for selected countries in the ECOWAS region - Ibrahima Diallo; Mamadou Abdoulaye Konté (West African Journal of Monetary and Economic Integration, 2022)
Monetary conditions index (MCI) has become an important indicator of monetary policy performance since its introduction by Bank of Canada in the 1990s. This is so, as the index allows central banks to gauge monetary policy stance and effectiveness. This paper builds an MCI for the seven (7) central banks in ECOWAS region, namely The Gambia, Ghana, Guinea, Liberia, Nigeria, Sierra Leone, and the UEMOA zone. The paper estimated a Dynamic Factor Model (DFM), complemented by Principal Component Analysis (PCA) to derive the weights of the variables in the MCI basket. Vector Autoregression (VAR) techniques are used for robustness analysis to assess the effectiveness of the computed MCIs as an indicator of monetary policy stance. In constructing the index, we consider three operating targets, namely interest rate, exchange rate, and reserve money, currently in use by central banks in the region. Key findings are that MCI can be effective to gauge monetary policy stance in West Africa, and thus presents the possibility of an alternative argument in the policy rule of central banks in the region.
Keywords: E52; E58; C32; 330; Monetary Policy; Monetary Conditions Index; Dynamic Factor Model; ECOWAS